Paneth-cell-disruption-induced necrotizing enterocolitis in mice requires live bacteria and occurs independently of TLR4 signaling - Jessica R. White; Huiyu Gong; Brock Pope; Patrick Schlievert; Steven J. McElroy (The Company of Biologists, 2017)
Necrotizing enterocolitis (NEC) remains a leading cause of morbidity and mortality in premature infants. Both human surgical specimens and animal models suggest a potential involvement of Paneth cells in NEC pathogenesis. Paneth cells play critical roles in epithelial homeostasis, innate immunity and host-microbial interactions. Yet, the complex interplay between Paneth cell disruption, epithelial barrier dysfunction and microbial-driven inflammation remains unclear in the immature intestine. In this study, mucosal intestinal injury consistent with human NEC was induced in postnatal day 14-16 (P14-P16) mice by disrupting Paneth cells, followed by gavage with Klebsiella pneumonia. Mucosal injury was determined by histology, serum cytokine levels and epithelial barrier dysfunction. Toll-like receptor 4 (TLR4) activation was examined using protein expression, gene expression, and TLR4−/− mice. Finally, the role of bacteria was evaluated using heat-killed bacteria, conditioned media, Bacillus cereus and cecal slurries. We found that live bacteria were required to induce injury; however, TLR4 activation was not required. NEC induced by Paneth cell disruption results in altered localization of tight junction proteins and subsequent loss of barrier function. Prior research has shown a requirement for TLR4 activation to induce NEC-like damage. However, many infants develop NEC in the absence of Gram-negative rod bacteremia, raising the possibility that alternative pathways to intestinal injury exist. In this study, we show a previously unknown mechanism for the development of intestinal injury equivalent to that seen in human NEC and that is not dependent on TLR4 pathways. These data are congruent with the new hypothesis that NEC may be the consequence of several disease processes ending in a final common inflammatory pathway.